Arthrodesis in the Charcot foot: a systematic review - Cianni, Luigi (Orthop Rev (Pavia), 2020)
The Charcot foot is a condition characterized by a progressive derangement of the foot. The type of deformity and patient clinical conditions will lead to the proper surgical approach among exostectomy, arthrodesis (through external and/or internal fixation) and amputation. Many authors report good clinical outcomes performing the arthrodesis in Charcot foot; however, the choice of the most appropriate hardware is still an issue. The aim of this study is to analyze the outcomes of different hardware in midfoot and hindfoot Charcot arthrodesis.